New faunistic data on Dolichopodidae (Diptera) from Turkey - S. Naglis (Кавказский энтомологический бюллетень, 2021)
Faunistic data is given for 83 species of Dolichopodidae from Turkey. The following genera are recorded for the first time in Turkey: Achalcus Loew, 1857, Cyrturella Collin, 1952, and Trigonocera Becker, 1902; 21 species are recorded for the first time in Turkey: Achalcus flavicollis (Meigen, 1824), Aphrosylus venator Loew, 1857, Asyndetus separatus (Becker, 1902), Chrysotus larachensis Grichanov, Nourti et Kettani, 2020, Cyrturella albosetosa (Strobl, 1909), Hydrophorus bipunctatus (Lehmann, 1822), Lamprochromus bifasciatus (Macquart, 1827), Lamprochromus kowarzi Negrobov et Tshalaja, 1988, Medetera petrophiloides Parent, 1925, M. signaticornis Loew, 1957, Orthoceratium sabulosum (Becker, 1907), Rhaphium antennatum (Carlier, 1835), Sciapus bellus (Loew, 1873), S. euchromus (Loew, 1857), S. longulus (Fallén, 1823), S. tenuinervis (Loew, 1857), Syntormon triangulipes Becker, 1902, Teuchophorus calcaratus (Macquart, 1828), Thinophilus quadrimaculatus Becker, 1902, Trigonocera rivosa Becker, 1902, Xanthochlorus silaceus Chandler et Negrobov, 2008.